2023
DOI: 10.3390/lubricants11030120
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Wear in Oscillating Grease-Lubricated Rolling Element Bearings of Different Size and Type

Abstract: Grease-lubricated rolling element bearings can suffer from wear due to lubricant starvation under certain oscillating operating conditions. Especially for large-scale slewing bearings, such as blade bearings in wind turbines, experimental investigations are complex compared to small-scale reference testing. For an easier manner of testing, it is desirable to know whether the results of small-scale testing are applicable to larger-sized bearings. In this work, three different bearing types were tested and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Oil release, base oil viscosity and shear thinning effects (structural viscosity) play a decisive role [11,16]. WANDEL has introduced the so-called Starvation Number to describe this risk of deficient lubrication [6,19], which is suitable, for considering blade bearings of wind turbines [15,19].…”
Section: State Of Research: Scientific Fundamentals Of Rolling Bearin...mentioning
confidence: 99%
“…Oil release, base oil viscosity and shear thinning effects (structural viscosity) play a decisive role [11,16]. WANDEL has introduced the so-called Starvation Number to describe this risk of deficient lubrication [6,19], which is suitable, for considering blade bearings of wind turbines [15,19].…”
Section: State Of Research: Scientific Fundamentals Of Rolling Bearin...mentioning
confidence: 99%
“…The main shaft bearing of wind turbines, as a special bearing, generally uses grease as a lubricant [5]. For greases, the study of rheology has become an important field.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that the bearing in an oscillation condition behaves differently from that in rotating, and the oscillation factor aosc was introduced to consider the difference. Both [6] and [7] indicated that the sequence and amplitude of an oscillation movement play an important role in wear occurrence.…”
Section: Introductionmentioning
confidence: 99%